The Effect of Personal Independence on Entrepreneurial Behavior (Case Study on Clothing Traders in Medan Petisah Market) - Christina Matiur Aruan (Institute of Computer Science (IOCS), 2021)
This research was conducted with the aim of finding out if there is an influence of personal independence on entrepreneurial behavior in clothing traders Pasar PetisahMedan. The research method used is a descriptive analysis method, and uses a simple linear regression analysis method. The data used in this study are primary and secondary data. The population in this study amounted to 69 people with sampling techniques using the purposive random sampling method. Data is processed statistically using spss for windowsprogramtools. The results of this study show that personal independence has a positive and significant effect on entrepreneurial behavior.